Evaluation of auditory performance of the aged on speech discrimination skills in south-west, Nigeria (2014)
As age increases, word recognition and speech discrimination ability systematically decreases, in relation to decline along the auditory systems leading to a reduction in the ability to perceive high pitched sounds and discriminate speech correctly. Thus, this study evaluated the performance of two categories of aged on speech discrimination skills. The study was carried out through Pure- Tone Audiometric Test (PTA) and Speech Discrimination Test (SDT) based on phonetically balanced words. Two hundred and forty (240) aged comprising two groups of one hundred and twenty (120) each of rural and urban dwellers were selected using purposive sampling technique. With the aid of independent t-test statistics at 0.05 level of significance, the findings revealed a significant difference in the hearing sensitivity between the aged in rural and urban areas across the pure-tone audiometric tested frequencies (t.cal = 4.20; P < 0.05). The aged in urban area had a significantly better performance on the speech. discrimination test than their counterparts in rural area (t.cal. = 3.78; P < 0.05). The study found no significant difference in the performance of the two groups on speech discrimination test in line with their gender make-up (t.cal. = 0.57; P> 0.05). Based on the findings, the study establishes that the two categories of aged demonstrated poor speech discrimination abilities as a result of their reduced hearing efficiency as a consequence of ageing. Recommendations were therefore made to the aged and their family, society, rehabilitation experts (support services) and government on the need to sharpen the aged verball non-verbal and interpersonal oral communication abilities as well as to curtail the explosion of hearing disability as a result of ageing in Nigeria.